Influential publications in sudden hearing loss: a bibliometric and visual synopsis of the top 100 cited articles - Xueshi Di; Junjie Liang; Xinru Wang; Xue Bai; Chongyang Zhang; Ting Pan; Tiantian He; Peng Bai (Frontiers in Neurology)
BackgroundSudden hearing loss (SHL) is a prevalent emergency in otolaryngology. Despite its frequency, there is a lack of econometric analysis and visualisation of the most significant SHL research literature. This study aims to provide a comprehensive overview and explore the characteristics of the 100 most cited articles in SHL through bibliometric analysis.Materials and methodsThe Web of Science Core Collection (WOSCC) was used to identify the 100 most cited SHL articles from 1999 to 2024. Tools such as CiteSpace and VOSviewer were employed to visualise data on countries, institutions, authors, co-cited authors, journals, co-cited journals, co-cited references, and keywords.ResultsThe citations of the 100 most cited articles ranged from 59 to 760, with publications spanning from 1999 to 2021 and peaking in 2005. The most cited article was authored by Schwartz SR. The majority of these articles originated from the United States. Key themes identified include treatment options for SHL, with prominent keywords such as deafness, therapy, and dexamethasone.ConclusionThis study identified the highly cited literature in SHL research, revealing a primary focus on treatment options. These findings provide crucial insights into the research hotspots and frontiers in the field of SHL.